Ultrastructure of early amelogenesis in wild‐type, Amelx‐/‐, and Enam‐/‐ mice: enamel ribbon initiation on dentin mineral and ribbon orientation by ameloblasts. Issue 6 (16th October 2016) - Smith, Charles E.; Hu, Yuanyuan; Hu, Jan C.‐C.; Simmer, James P.
Abstract: Introduction: Dental enamel is comprised of highly organized, oriented apatite crystals, but how they form is unclear. Methods: We used focused ion beam (FIB) scanning electron microscopy (SEM) to investigate early enamel formation in 7‐week‐old incisors from wild‐type, Amelx ‐/‐, and Enam ‐/‐ C56BL/6 mice. FIB surface imaging scans thicker samples so that the thin enamel ribbons do not pass as readily out of the plane of section, and generates serial images by a mill and view approach for computerized tomography. Results: We demonstrate that wild‐type enamel ribbons initiate on dentin mineral on the sides and tips of mineralized collagen fibers, and extend in clusters from dentin to the ameloblast membrane. The clustering suggested that groups of enamel ribbons were initiated and then extended by finger‐like membrane processes as they retracted back into the ameloblast distal membrane. These findings support the conclusions that no organic nucleator is necessary for enamel ribbon initiation (although no ribbons form in the Enam ‐/‐ mice), and that enamel ribbons elongate along the ameloblast membrane and orient in the direction of its retrograde movement. Tomographic reconstruction videos revealed a complex of ameloblast membrane processes and invaginations associated with intercellular junctions proximal to the mineralization front and also highlighted interproximal extracellular enamel matrix accumulations proximal to the interrod growth sites, which we propose are important for expanding the interrod matrix and extending interrod enamel ribbons. Amelx ‐/‐ mice produce oriented enamel ribbons, but the ribbons fuse into fan‐like structures. The matrix does not expand sufficiently to support formation of the Tomes process or establish rod and interrod organization. Conclusion: Amelogenin does not directly nucleate, shape, or orient enamel ribbons, but separates and supports the enamel ribbons, and expands the enamel matrix to accommodate continued ribbon elongation, retrograde ameloblast movement, and rod/interrod organization. Abstract : This is the first report using focused ion beam microscopy to visualize enamel ribbons at high resolution as they form, which are shown to initiate on the underlying dentin crystals. This continuity between dentin and enamel mineral has been difficult to establish with conventional thin sectioning techniques and has been debated for many years. We converted serial images into movies that allowed us to better appreciate the complex infolding of cell membranes and intercellular compartmentalization that are integral to the complex mechanism of enamel biomineralization.